Differentiation of pityriasis rubra pilaris from plaque psoriasis by dermoscopy - Abhijeet Kumar Jha; Aimilios Lallas; Sidharth Sonthalia; Deepak Jakhar; Uday K. Udayan; R. K. P. Chaudhary (Mattioli1885, 2018)
Background: Diagnosing and differentiating pityriasis rubra pilaris (PRP) from other disorders can be a challenging task. Although histopathology remains the gold standard, it may not be feasible at times, especially in children. Being noninvasive, dermoscopy can be of great diagnostic importance in such a scenario. Dermoscopy overcomes the refractive properties of stratum corneum by interface medium or cross-polarization enabling easier visualization of lesions. Objective: To study the dermoscopic features of PRP and compare them with dermoscopic features of psoriasis. Patients and Methods: Retrospective observational analysis of dermoscopic characteristics of 28 patients with PRP (16) and psoriasis (12). Polarized dermoscopy at 10× magnification was performed and photographs were captured by Apple iPhone 7. The selection of dermoscopic variables was based on preexisting literature on the dermoscopic patterns of the 2 entities. Results: The most frequent dermoscopic criteria of PRP were the presence of a central hair (16/16; 100%), follicular plugs (11/16; 68.7%), and perifollicular yellow/orange halos (9/16; 56.2%). No vascular structures were seen in our cases of PRP. Psoriasis was characterized by regularly distributed dotted vessels (12/12; 100%) and white scales (8/12; 66.6%). Conclusions: Round-to-oval yellowish areas surrounding a central hair with or without follicular plugs represents the most frequent dermoscopic pattern of PRP.